Climate change, consumption and intergenerational justice : lived experiences in China, Uganda and the UK /: lived experiences in China, Uganda and the UK. (2019) - Diprose, Kristina; Valentine, Gill, 1965-; Vanderbeck, Robert M; Liu, Chen; McQuaid, Katie
No abstract available